2018
DOI: 10.1017/s0033291718000740
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation in victims of childhood abuse or neglect: a meta-analytic review

Abstract: Childhood abuse and neglect are associated with dissociative symptoms in adulthood. However, empirical studies show heterogeneous results depending on the type of childhood abuse or neglect and other maltreatment characteristics. In this meta-analysis, we systematically investigated the relationship between childhood interpersonal maltreatment and dissociation in 65 studies with 7352 abused or neglected individuals using the Dissociative Experience Scale (DES). We extracted DES-scores for abused and non-abused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(105 citation statements)
references
References 104 publications
6
92
2
5
Order By: Relevance
“…This is in line with a recent meta-analytic review (Vonderlin et al, 2018) that also found CSA to be especially strongly related to dissociation, when compared to neglect and emotional abuse. CSA has also been identified as a potent risk factor for auditory hallucinations (Bentall et al, 2014), which are conceptualized as a symptom of TRASC in the 4-D model.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with a recent meta-analytic review (Vonderlin et al, 2018) that also found CSA to be especially strongly related to dissociation, when compared to neglect and emotional abuse. CSA has also been identified as a potent risk factor for auditory hallucinations (Bentall et al, 2014), which are conceptualized as a symptom of TRASC in the 4-D model.…”
Section: Discussionsupporting
confidence: 90%
“…A review of research on the development of dissociation would be incomplete without clear acknowledgement of maltreatment as an aetiological factor. Compelling evidence supports the relationship between maltreatment and dissociation, as most recently meta-analysed by Vonderlin et al (2018). The authors synthesized the findings of 65 crosssectional studies (n = 7352) that investigated links between maltreatment (abuse and neglect) and dissociation, as measured by self-report.…”
Section: Research On Childhood Maltreatment and Dissociationmentioning
confidence: 99%
“…Nevertheless, the link between dissociation and suggestibility remains controversial in part because many researchers conflate elevated suggestibility with proneness to false memories rather than conceptualizing it as a multidimensional cognitive-perceptual function. Furthermore, suggestibility does not reliably correlate with dissociation in the general population (Alganami et al, 2017; P. V. Butler & Bryant, 1997;Dienes et al, 2009), and it has a mixed relationship with trauma exposure (Eisen & Carlson, 1988;Nash & Lynn, 1985;Rhue et al, 1990), which is widely considered to be the principal antecedent of dissociation (Dalenberg et al, 2012;Vonderlin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%